2014
DOI: 10.1016/j.juro.2013.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of Pubertal Children and Postpubertal Adolescents with Clinical Stage I Testicular Nonseminomatous Germ Cell Tumors

Abstract: Approximately half of pubertal children and postpubertal adolescents with high risk clinical stage I testicular germ cell tumors harbor occult metastatic disease. These results may be useful when discussing prognosis and treatment with patients and families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In prepubertal boys younger than 5 years, testicular tumors are different from adult neoplasms. Germ cell tumors are less common than in adults and account for 60-77% of the testicular tumors [3][4][5][6] [7].…”
Section: Mmentioning
confidence: 99%
“…In prepubertal boys younger than 5 years, testicular tumors are different from adult neoplasms. Germ cell tumors are less common than in adults and account for 60-77% of the testicular tumors [3][4][5][6] [7].…”
Section: Mmentioning
confidence: 99%
“…Even patients with high-risk pathologic features on the orchiectomy specimen (440%-50% EC histology or lymphovascular invasion [LVI]) can consider surveillance. In a series of adolescents with Clinical Stage I TGCT 58.3% of patients with "high-risk" pathology relapsed, vs. 0% of the patients without "high-risk" features [30]. Similarly, in a study of 248 men in New Zealand with Clinical Stage I disease, overall 28% relapsed: 46% with LVI relapsed vs. 17% without LVI.…”
Section: Postpubertal Stage Ia and Ib Diseasementioning
confidence: 92%
“…EC may also produce AFP. Overall, EC is an aggressive histology frequently associated with metastases and has been used for risk stratification of Clinical Stage I disease in both adolescents and adults [29,30].…”
Section: Nonseminomatous Germ Cell Tumorsmentioning
confidence: 99%
“…In the adult population, the identification of high-risk features for harboring of occult metastases—lymphovascular invasion and an increasing component of embryonal carcinoma for NSGCT [ 35 ] and size > 4 cm and rete testis invasion for seminoma [ 36 ]—has allowed a risk-stratified treatment approach to be employed [ 34 ]. Cost et al [ 37 ] reviewed 23 patients aged 7–21 years and found that about half of all patients had high-risk features (≥40% embryonal carcinoma or lymphovascular invasion), and almost 60% with high-risk features harbored occult metastatic disease. No patients without high-risk features had metastatic disease.…”
Section: Disease-specific Aspects Unique To the Aya Populationmentioning
confidence: 99%